2016
DOI: 10.1111/1745-9125.12106
|View full text |Cite
|
Sign up to set email alerts
|

How Judges Think About Racial Disparities: Situational Decision‐making in the Criminal Justice System*

Abstract: Researchers have theorized how judges’ decision‐making may result in the disproportionate presence of Blacks and Latinos in the criminal justice system. Yet, we have little evidence about how judges make sense of these disparities and what, if anything, they do to address them. By drawing on 59 interviews with state judges in a Northeastern state, we describe, and trace the implications of, judges’ understandings of racial disparities at arraignment, plea hearings, jury selection, and sentencing. Most judges i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
65
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 54 publications
(66 reference statements)
1
65
0
Order By: Relevance
“…They found that workgroup members generally agreed trial penalties were a way to encourage guilty pleas; that pleas were viewed as a sign of remorse; and that pleading led to a less‐severe penalty at least in part because it allowed the defendant to avoid “emotional reactions to ‘ugly facts’” that often come out in trial (Ulmer and Kramer, : 396). Most recently, Clair and Winter () employed judge interviews to explore different strategies trial judges use to address racial disparities in various phases of the judicial process. Along these lines, qualitative inquiry was especially appealing for the current project given the findings related to county‐level variation uncovered in prior research and, more generally, given that little exists theoretically on the question of what factors and features might make a jurisdiction more likely to exhibit greater statewide legal culture.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that workgroup members generally agreed trial penalties were a way to encourage guilty pleas; that pleas were viewed as a sign of remorse; and that pleading led to a less‐severe penalty at least in part because it allowed the defendant to avoid “emotional reactions to ‘ugly facts’” that often come out in trial (Ulmer and Kramer, : 396). Most recently, Clair and Winter () employed judge interviews to explore different strategies trial judges use to address racial disparities in various phases of the judicial process. Along these lines, qualitative inquiry was especially appealing for the current project given the findings related to county‐level variation uncovered in prior research and, more generally, given that little exists theoretically on the question of what factors and features might make a jurisdiction more likely to exhibit greater statewide legal culture.…”
Section: Methodsmentioning
confidence: 99%
“…For notable exceptions of contemporary qualitative research related to courts, see Clair and Winter (); King et al. (); Ulmer (); Ulmer and Kramer (); and Wright and Levine ().…”
mentioning
confidence: 99%
“…Lynch (), for example, demonstrated how parole officers resented a revised characterization of their work identities based on efficient record‐keeping and actuarial methods. Others further mapped how support for new mandates varies across positions (Rudes, ) or situations (Clair and Winter, ; Steiner, Travis, and Makarios, ), and how the “instrumental impact” of policy is contingent on the alignment among local agencies and communities (Grattet and Jenness, ) and the centrality of the reforms to local workgroups (Lynch and Omori, ).…”
Section: Limits Of Policy Change In Correctionsmentioning
confidence: 99%
“…A robust set of studies has consistently drawn attention to context and agency as key moderators of the relationship between “law on the books” and “law in action” (see, e.g., Clair and Winter, ; Grattet and Jenness, ; Lynch and Omori, ; Nagel and Schulhofer, ; Rudes, ; Verma, ). This dual focus has been proposed by researchers as a way to identify mechanisms of local policy implementation and as a way to map methods for introducing and sustaining organizational change.…”
Section: Limits Of Policy Change In Correctionsmentioning
confidence: 99%
See 1 more Smart Citation